P8 Where do patients go for chlamydia testing within non-gum community settings and what proportion of re-testers shows venue loyalty?. (18th May 2015) - Harb, Ana; Town, Katy; Hollis, Emma; Lowndes, Catherine; Dunbar, Kevin
Abstract : Background/introduction: The English National Chlamydia Screening Programme focuses on prevention, control and treatment of chlamydia in sexually active under-25 year olds. A greater understanding of where young adults attend services helps to inform commissioners of where to focus resources within community settings. Aim(s)/objectives: To investigate whether young people return to the same type of primary care / community (i.e. non-Genitourinary Medicine) service for re-testing. Methods: Surveillance data from the Chlamydia Testing Activity Dataset (CTAD) was used to identify patient attendances at primary care / non GUM community services among 15 to 24 year olds and monitor re-testing within and between community services. Results: From January 2012 to December 2013, 1, 333, 718 young people underwent 1, 626, 106 chlamydia tests. The majority of people (84%) were tested only once. Of those who tested more than once, 57% used the same venue type. General Practice (GP) was the most commonly re-attended service for patients who tested twice (55.3%). Among those who tested three or four times, there was an increasing preference for community sexual health services (50% and 57% respectively). Discussion: Patients re-attended GP services more often than other venue types but for subsequent attendances more specialised community sexual health services were used. Very few repeat visits were made to pharmacies or pregnancy termination services. These data show that patients are likely to return to services they know when they require a further test. This should be taken into consideration by commissioners implementing new retesting guidance from the NCSP.